Patterns of species richness and endemism of butterflies and day-flying moths in the monsoon tropics of northern Australia. (January 2020) - Braby, M.F.; Williams, M.R.; Coppen, R.A.M.; Williams, A.A.E.; Franklin, D.C.
Abstract: Patterns of species richness and endemism were analyzed for 154 resident/breeding diurnal Lepidoptera in 153 grid cells (100 km × 100 km) based on a recently published set of spatial distribution maps (range-map and atlas data) in the western and central Australian Monsoon Tropics biome of northern Australia ( 1.2 million km 2 ). Biodiversity hotspots were then identified on the basis of coincidence of high values of species richness, endemic richness and weighted endemism. Spatial and environmental variables accounting for significant variation in species and endemic richness were determined using multivariate generalized linear models. Broad patterns of species and endemic richness showed a pronounced north-south latitudinal gradient that was significantly correlated with mean annual rainfall, from the wetter northern coastal areas to the drier southern inland areas of the semi-arid zone. Analysis of weighted endemism identified three putative centers of endemism: the Top End (north-western corner), the Kimberley (northern) and Arnhem Land (Gove Peninsula). Overall, the north-western corner of the Top End (86, 860 km 2 ) – including the Arnhem Land Plateau (Kakadu NP-Nitmiluk NP and Warddeken IPA), reserves in the Darwin region, Litchfield NP, the Tiwi Islands, Fish River-Daly River, and Cobourg Peninsula (Garig Gunak Barlu NP) – is a major biodiversity hotspot for the conservation of diurnal Lepidoptera based on congruent patterns of species richness, endemic richness and weighted endemism. Large discrepancies between actual survey lists (atlas data) and inferred lists (range-map data) indicate the need for further inventory of the National Reserve System, particularly for several reserves identified as significant for diurnal Lepidoptera diversity (Marri-Jabin IPA, Djukbinj NP, Warddeken IPA and Nitmiluk NP).